2017
DOI: 10.1016/j.jpolmod.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Danger: Local corruption is contagious!

Abstract: Corruption is a major problem, and not only in developing countries. It impedes economic growth, weakens the rule of law and undermines the legitimacy of institutions. Although it has been studied at national level from different perspectives, there is a recent growing body of research on local corruption. As far as we know, these latter studies focused on corruption and its effects on votes. However, a further question arises as to whether there is a mimetic effect on neighbouring municipalities? We employ da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…This suggests that larger subnations have lower corruption levels than smaller subnations. This finding is in line with Seldadyo & de Haan (2006) and Lopez-Valcarcel et al (2017), which find that corruption levels increase with population density. Larger subnations are likely to have lower population densities than smaller subnations, which makes citizens of larger subnations less anonymous.…”
Section: The Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that larger subnations have lower corruption levels than smaller subnations. This finding is in line with Seldadyo & de Haan (2006) and Lopez-Valcarcel et al (2017), which find that corruption levels increase with population density. Larger subnations are likely to have lower population densities than smaller subnations, which makes citizens of larger subnations less anonymous.…”
Section: The Resultssupporting
confidence: 91%
“…Recent empirical literature indicates that a similar spatial process works at subnational level. Dong & Torgler (2012), Bologna (2017) and Lopez-Valcarcel, Jiménez & Perdiguero (2017) find spatial interdependencies in the corruption levels of Brazilian municipalities, Spanish municipalities and Chinese provinces, respectively.…”
Section: Introductionmentioning
confidence: 94%
“…In theory, scandals such as these could perturb beliefs in a direction conducive to the spread of corruption along the lines of what we found with our subjects in Costa Rica. Outside of the Americas, Spain, which has experienced an unprecedented wave of corruption scandals over the last decade (Lopez‐Valcarcel, Jiménez, and Perdiguero ), would be another country for which the dynamics identified in this article may apply. The existence of these similar cases notwithstanding, an important task for future research is to sort out the degree to which the results encountered here extend to polities where corruption levels and expectations are relatively more stable than in Costa Rica.…”
Section: Resultsmentioning
confidence: 99%
“…Using state‐level U.S. data from 1995 to 2004, Goel and Nelson () also find evidence of corruption neighborhood effects. Lopez‐Valcarcel, Jiménez, and Perdiguero () similarly find evidence that corruption is contagious using a data set of local Spanish municipalities from 2001 to 2010. Studies by Becker, Egger, and Seidel () and Goel and Saunoris () utilize cross‐national data to estimate the degree to which corruption in one country affects its neighbors.…”
Section: Empirical Studies Of Corruption Spilloversmentioning
confidence: 88%
“…The findings are that the impact is limited unless media coverage is broad (Fernández-Vázquez and Rivero 2010; Costas-Pérez et al 2012) and that the impact varies depending on whether the party revealed as being corrupt is on the left or right of the political ideological spectrum (Jiménez and García, 2018). Moreover, local corruption is contagious (González et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%